Low prevalence of insulin resistance among HIV-infected children receiving nonnucleoside reverse transcriptase inhibitor-based highly active antiretroviral therapy in Thailand - B. Lee (2018)
Background: Highly active antiretroviral therapy (HAART) is reported to cause insulin resistance among adults, but effects on children are less clear. We attempted to describe the prevalence of insulin resistance among HIV-infected children receiving HAART. Methods: Insulin resistance was assessed at 96 weeks of treatment with nonnucleoside reverse transcriptase inhibitor (NNRTI)-based HAART (nevirapine or efavirenz with stavudine and lamivudine) among children in Chiang Mai, Thailand. Insulin resistance was defined as homeostasis model assessment for insulin resistance (HOMA-IR) ≥ 3.16, fasting c-peptide ≥ 4.40ng/mL or fasting insulin ≥ 25.0μU/mL. Impaired fasting glucose (IFG) was defined as glucose ≥110mg/dL. Measurements were analysed for associations with age, lipodystrophy, treatment regimen and clinical data. Results: The prevalence of insulin resistance was 6.5% no child had IFG. Those with insulin resistance were older with higher body mass index. Children ≥ 10 years had higher HOMA-IR, c-peptide and insulin, but no difference was seen in the frequency of insulin resistance. No associations between insulin resistance and lipodystrophy or treatment regimen were detected. Conclusions: Insulin resistance is uncommon among children receiving NNRTI-based HAART and is unrelated to lipodystrophy. © 2009 British HIV Association.